A Triple-Difference Approach to Re-Evaluating the Impact of China’s New Cooperative Medical Scheme on Incidences of Chronic Diseases Among Older Adults in Rural Communities - Chen Q; Chu X; Wang S; Zhang B (Dove Medical Press, 2020)
Qihui Chen,1 Xueling Chu,2 Suzhen Wang,3 Bo Zhang4 1Center for Food and Health Economic Research, College of Economics and Management, China Agricultural University, Beijing, People’s Republic of China; 2Foreign Economic Cooperation Center, Ministry of Agriculture, Beijing, People’s Republic of China; 3School of Public Health, Weifang Medical University, Weifang, Shandong, People’s Republic of China; 4Department of Neurology and ICCTR Biostatistics and Research Design Center, Boston Children’s Hospital and Harvard Medical School, Boston, MA, USACorrespondence: Bo ZhangDepartment of Neurology and ICCTR Biostatistics and Research Design Center, Boston Children’s Hospital and Harvard Medical School, 21 Autumn Street, Suite 323, Boston, MA 02115, U.S.AEmail bo.zhang@childrens.harvard.eduSuzhen WangSchool of Public Health, Weifang Medical University, 7166 Baotong West Street, Weifang, Shandong 261053, People’s Republic of ChinaEmail wangsz@wfmc.edu.cnBackground: This paper re-evaluates the impacts of China’s New Cooperative Medicine Scheme (NCMS), a social health insurance program targeting China’s rural population, on the incidences of chronic diseases among its enrollees. Although coverage under the NCMS expanded rapidly following its implementation in 2003, previous studies have failed to reach a consensus on its health impacts. Existing conflicting results may be due to methodological problems such as implausible identification assumptions and the failure to focus on the most relevant beneficiaries.Methods: Drawing on data from a longitudinal sample from the China Health and Nutrition Survey (CHNS), we focus on a subgroup of patients over the age of 55 years to re-estimate the NCMS’s impact on incidences of chronic disease among enrollees. We adopt a triple-difference (difference-in-difference-in-differences) method, relaxing the parallel-trend assumption commonly invoked in the previous double-difference (difference-in-differences) studies.Results: Our triple-difference estimates suggest that the NCMS has significantly reduced the incidences of apoplexy and diabetes among rural residents aged 55 years or older. The impacts of the NCMS on chronic disease are underestimated by the commonly adopted double-difference method. The triple-difference method allows evaluations to focus on the most relevant subgroups for detecting program impacts.Conclusion: Our findings that the NCMS has significantly positive impacts on elderly enrollees’ incidences of chronic diseases also suggest the need for examining its impacts on other vulnerable groups, such as low-income individuals, young children, and individuals with poor health conditions.Keywords: impact evaluation, China, social health insurance programs, chronic diseases, difference-in-differences estimation, difference-in-difference-in-differences estimation, triple-difference estimation